2018
DOI: 10.1126/scisignal.aao4220
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of Wnt, growth factor, and heterotrimeric G protein signals on the guanine nucleotide exchange factor Daple

Abstract: Cellular proliferation, differentiation, and morphogenesis are shaped by multiple signaling cascades; their concurrent dysregulation plays an integral role in cancer progression and is a common feature of many malignancies. Three such cascades that contribute to the oncogenic potential are those mediated by Wnt and Frizzled (FZD), growth factor receptor tyrosine kinases (RTKs), and trimeric G proteins and GPCRs. Daple is a Dishevelled (Dvl)- and FZD-binding protein and a guanine-nucleotide exchange factor (GEF… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 81 publications
(162 reference statements)
4
38
0
Order By: Relevance
“…First discovered in a yeast-two hybrid screen through its ability to bind to the PDZ domain on Disheveled (Dvl), Daple has emerged as a key modulator of Wnt signaling [9,11]. The extreme C-terminus on Daple contains an 'atypical' PBM which we, and others, demonstrated to be necessary for the Daple•Dvl interaction [10][11][12]. We subsequently showed that Daple binds Gαi proteins and triggers GTPase signaling downstream of the Wnt receptor Frizzled-7 upon activation by Wnt5a; such signaling is necessary for the activation of the b-catenin-independent Wnt signaling pathway (a.k.a.…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…First discovered in a yeast-two hybrid screen through its ability to bind to the PDZ domain on Disheveled (Dvl), Daple has emerged as a key modulator of Wnt signaling [9,11]. The extreme C-terminus on Daple contains an 'atypical' PBM which we, and others, demonstrated to be necessary for the Daple•Dvl interaction [10][11][12]. We subsequently showed that Daple binds Gαi proteins and triggers GTPase signaling downstream of the Wnt receptor Frizzled-7 upon activation by Wnt5a; such signaling is necessary for the activation of the b-catenin-independent Wnt signaling pathway (a.k.a.…”
Section: Introductionmentioning
confidence: 87%
“…We began by asking if the newly discovered Daple•PARD3-PDZ interaction affects the Daple•Gai interaction. We had previously described an unexpected allosteric phenomenon in which the Daple•Dvl-PDZ and the Daple•Gai interactions are mutually exclusive, i.e., ternary complexes between all 3 proteins, Gai•Daple•Dvl is not feasible [10]. To our surprise, such allostery was not observed in the case of PARD3; instead, we found that Gai3 bound PARD3 exclusively in the presence of Daple, and not directly, indicative of the formation of tertiary Gai•Daple•PARD3 complexes (Figure 5G).…”
Section: Daple Pard3 and G Protein Can Form Ternary Complexesmentioning
confidence: 99%
See 3 more Smart Citations